The Influence of the European Union on Ukraine’s Anti-Corruption Reforms, 2014-2024 - Hryshko, Daria (2025)
This bachelor’s thesis examines how the European Union influenced anti-corruption reforms in Ukraine between 2014 and 2024. Focusing on three major reforms—NABU, the asset declaration system, and the High Anti-Corruption Court—the study analyzes how Ukrainian political elites responded to EU conditionality. Using process tracing and qualitative methods, the thesis identifies three elite strategies: bureaucratic stalling, Potemkin reforms, and strategic co-optation. The findings contribute to understanding the complex interplay between external pressure and internal resistance in post-Maidan Ukraine.